Penguatan Ekonomi Dalam Negeri dalam Menghadapi Persaingan Global : Relevansi Kebijakan Ekonomi Umar bin Khathab - Asep Saefurrohman (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2017)
Umar bin Khathab is the second khalifah that success for bringing Islam to the victory with a variety of foreigh steps that implemented in lead Islam. Not except in economics problem and relation diplomatic that he form with some state and kingdom at that time. At Khalifah Umar bin Khathab era, they do reconstruction on baitul mal as country treasure, and arrange society economical problems from all aspect that relation with economic development as education, investment, infrastructure, and development of human resources. The writer explain condition of economic and foreigh of khalifah Umar bin Khathab in consolidate country economic to face market rivalry that more open end and wide together with wider of region that enter under Islamic administration.